Dysfunction of Caveolae‐Mediated Endocytic TβRI Degradation Results in Hypersensitivity of TGF‐β/Smad Signaling in Osteogenesis Imperfecta. (17th November 2022) - Shi, Changgui; Sun, Bin; Wu, Huiqiao; Zhang, Rongcheng; Wu, Lecheng; Guo, Lei; Li, Changwei; Xi, Yanhai; Yuan, Wen; Zhang, Ying; Xu, Guohua
ABSTRACT: Osteogenesis imperfecta (OI) is a genetic disorder caused by mutations of type I collagen‐related genes, and excessive transforming growth factor‐beta (TGF‐β) signaling is a common mechanism. TGF‐β/Smad signaling has inhibitory effects on osteoblast differentiation and maturation and is mainly transduced and regulated by the internalization of a tetrameric receptor complex comprising types I and II TGF‐β receptors (TβRI and TβRII). During internalization, clathrin‐mediated endocytosis enhances TGF‐β/Smad signaling via Smad2/3 phosphorylation and receptors recycling, while caveolae‐mediated endocytosis turns off TGF‐β/Smad signaling by promoting receptor ubiquitination and degradation. In this study, using an animal model of OI (Colla2 oim, osteogenesis imperfecta murine [oim]/oim mouse), we found that osteoblastic cells of oim/oim mice were more sensitive to the inhibitory effects of TGF‐β on osteoblast differentiation and maturation and had much higher cell membrane protein levels of TGF‐β receptors than those of wild‐type (wt)/wt mice. Further results showed that clathrin‐mediated endocytosis of TβRI was enhanced, whereas caveolae‐mediated TβRI endocytic degradation was reduced in oim/oim mice, combined with reduced caveolin‐1 (Cav‐1) phosphorylation. In addition, type I collagen downregulated TβRI via focal adhesion kinase (FAK) and Src activation‐dependent Cav‐1 phosphorylation. To further examine this mechanism, 4‐week‐old oim/oim and wt/wt mice were treated with either TβRI kinase inhibitor (SD‐208) or vehicle for 8 weeks. SD‐208 treatment significantly reduced the fracture incidence in oim/oim mice. Micro–computed tomography and biomechanical testing showed that femoral bone mass and strength were significantly improved with SD‐208 treatment in both genotypes. Additionally, SD‐208 significantly promoted osteoblast differentiation and bone formation and inhibited bone resorption. In conclusion, dysfunction of caveolae‐mediated endocytic TβRI degradation is a possible mechanism for the enhanced TGF‐β/Smad signaling in OI. Targeting this mechanism using a TβRI kinase inhibitor effectively reduced fractures and improved bone mass and strength in OI model and, thus, may offer a new strategy for the treatment of OI. © 2022 American Society for Bone and Mineral Research (ASBMR). Abstract : In this study, we found that caveolae‐mediated endocytic TβRI degradation was reduced in OI due to the impaired regulation of type I collagen on FAK/Src activation‐dependent Caveolin‐1 phosphorylation, which further enhanced the TGF‐β/Smad signaling on the inhibition of osteoblast differentiation. Inhibition of TβRI kinase by SD‐208 effectively reduced fractures and improved bone mass and strength in an OI mouse model.